Adolescence, pregnancy and abortion : constructing a threat of degeneration - Macleod, Catriona (Women and psychology, 2011)
Why, despite evidence to the contrary, does the narrative of the negative consequences of teenage pregnancy, abortion and childbearing persist? This book outlines a critical view of 'teenage pregnancy' and abortion, arguing that the negativity surrounding early reproduction is underpinned by a particular understanding of adolescence